2016
DOI: 10.17116/hirurgia2016245-50
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular arterial embolization for duodenal bleeding as an alternative to surgical approach

Abstract: TAE is effective to control bleeding and reduces mortality rate especially in high risk and elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This is consistent with the opinion that interventions aimed at a long-term full patency of the treated vessel are less useful, as even temporary recanalization improves blood flow in the foot, and this promotes healing of wounds or ulcers ( 8 ). It is known that oxygen demand of the healed tissues decreases and normally lower blood flow is required to keep the tissue intact ( 9 ). Taking into account the fact that repeated stenting and balloon angioplasty can be performed, they have an undoubted advantage over bypass and prosthetic vascular interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the opinion that interventions aimed at a long-term full patency of the treated vessel are less useful, as even temporary recanalization improves blood flow in the foot, and this promotes healing of wounds or ulcers ( 8 ). It is known that oxygen demand of the healed tissues decreases and normally lower blood flow is required to keep the tissue intact ( 9 ). Taking into account the fact that repeated stenting and balloon angioplasty can be performed, they have an undoubted advantage over bypass and prosthetic vascular interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggetsed that TAE is a safe treatment method for gastrointestinal bleeding. Authors have reported satisfactory results of TAE compared to surgery for treatment of bleeding after gastric cancer resection, duodenal bleeding, severe bleeding of upper gastrointestinal tumors and bleeding gastroduodenal ulcers [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%